2016
DOI: 10.1136/jnnp-2015-312940
|View full text |Cite
|
Sign up to set email alerts
|

Extended interval dosing of natalizumab in multiple sclerosis

Abstract: Dosing intervals up to 8 weeks 5 days did not diminish effectiveness of NTZ therapy. Further monitoring is ongoing to evaluate if the risk of PML is reduced in patients on EID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 26 publications
8
113
0
2
Order By: Relevance
“…The risk of developing progressive multifocal leukoencephalopathy (PML) in a John Cunningham virus antibodynegative natalizumab-treated patient is estimated at 1: 10,000 36 and may be further reduced with extended interval dosing. 37 Natalizumab is otherwise generally well tolerated with a paucity of other potential side effects. In a population with rheumatoid arthritis, the risk of rituximab with long-term use is estimated to be 1:30,000.…”
Section: The Reported Safety Profiles Of Some Highly Effective Agentsmentioning
confidence: 99%
“…The risk of developing progressive multifocal leukoencephalopathy (PML) in a John Cunningham virus antibodynegative natalizumab-treated patient is estimated at 1: 10,000 36 and may be further reduced with extended interval dosing. 37 Natalizumab is otherwise generally well tolerated with a paucity of other potential side effects. In a population with rheumatoid arthritis, the risk of rituximab with long-term use is estimated to be 1:30,000.…”
Section: The Reported Safety Profiles Of Some Highly Effective Agentsmentioning
confidence: 99%
“…The likelihood of developing PML is linked to certain risk factors including treatment duration, prior treatment with immunosuppressants and John Cunningham virus (JCV) serostatus . Recently, it has been suggested that a higher NTZ concentration (resulting in higher α‐4‐integrin receptor saturation) might be an additional risk factor for the development of PML . Although it is not confirmed that a higher NTZ concentration leads to an increased risk of PML, some neurologists are extending NTZ dose intervals with the aim of lowering the risk of PML .…”
Section: Introductionmentioning
confidence: 99%
“…Extended interval dosing (EID) of natalizumab is an attempt to target a level of α4β 1 receptor saturation that maintains drug clinical effectiveness with the least effect possible on immunosurveillance in order to lower the PML risk. A retrospective chart review examined outcomes for 905 patients on EID versus 1,099 patients on standard interval dosing (SID) 55. In this analysis, EID ranged from dosing every 4 weeks 3 days to dosing every 8 weeks 5 days.…”
Section: Natalizumab Safety and Tolerabilitymentioning
confidence: 99%